The Theory of Planned Behaviour and the Entrepreneurial Event Model as predictive models of entrepreneurial intention - Davids, Fawwaaz (Organisational Psychology, 2018)
The Theory of Planned Behaviour and The Entrepreneurial Event Model were used as models to predict entrepreneurial intention amongst final year students. The sufficiency of this paradigm was compared with the aim of determining which model predicts entrepreneurial intention the most within a South African context. A sample of 186 students was used to determine the sufficiency of the Theory of Planned Behaviour. As part of our methodology, a sub-set (n = 123) of the sample was used to determine the sufficiency of the Entrepreneurial Event Model. The sample consisted of final year commerce and engineering students. The results of the regression analysis indicated that the Theory of Planned Behaviour explained 58% of the variance in entrepreneurial intention. The Entrepreneurial Event Model was found to be less sufficient than the Theory of Planned Behaviour and only explained 38% of the variance in entrepreneurial intention. Therefore, when predicting entrepreneurial intention in a South African context, the Theory of Planned Behaviour can be considered the more sufficient model of prediction. Future research should consider using the Theory of Planned Behaviour, rather than Entrepreneurial Event Model, for entrepreneurial intention prediction among students in South Africa.